Cavernous sinus involvement in human papillomavirus associated oropharyngeal squamous cell carcinoma: case report of an atypical site of distant metastasis - David Forner; Derek Wilke; Matthew H. Rigby; Sidney Croul; Anuradha Mishra; Emad Massoud; David B. Clarke; Nathan Lamond (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background HPV-associated OSCC (HPV-OSCC) has been determined to be a distinct disease entity from non-HPV associated OSCC. Patients affected by HPV-OSCC generally have a more favourable prognosis, with improved rates of locoregional control and survival compared with their non-HPV counterparts. Despite this, HPV-OSCC has a similar rate of distant metastases. Interestingly, recent evidence has emerged that demonstrates more frequent atypical metastasis patterns when compared to non-HPV associated disease. To the best of our knowledge, this report describes the first case of a confirmed HPV-OSCC with distant metastasis to the cavernous sinus. Case Presentation A 62-year-old non-smoking male presented to the head and neck oncology clinic with a five-month history of enlarging right neck mass causing neck pain, dysphagia, and dysphonia. HPV-associated base of tongue squamous cell carcinoma (cT4aN2c) was diagnosed, and he was treated with primary chemoradiation. Shortly after treatment, he presented with progressive bilateral cranial nerve palsies including left cranial nerve III and right cranial nerve VI involvement. Imaging identified masses in the left cavernous sinus with extension of tumor into the sella and in the right cavernous sinus at the level of Dorello’s canal. Endoscopic Image Guided Transsphenoidal biopsy of the left sellar mass confirmed distant metastases from the previously treated HPV-OSCC primary to the cavernous sinus. The patient was palliated with carboplatin and paclitaxel. Conclusion The presented report is the first documented case of confirmed HPV-associated oropharyngeal squamous cell carcinoma metastasizing to the cavernous sinus, and the only HPV confirmed head and neck cancer case to present with metastasis to the cavernous sinus and limited extracranial disease. This case demonstrates the importance of recognizing presentations of atypical metastasis that are possible in HPV-associated oropharyngeal cancer. Given the rarity of metastasis to this region, vigilance in follow up is instrumental in early identification and treatment for these patients.